A randomized, controlled 24-week study of intermittent subcutaneous interleukin-2 in HIV-1 infected patients in Thailand - Kiat Ruxrungtham (2018)
Objectives: To assess the immunological and virological effects, safety profile and feasibility of subcutaneous interleukin-2 (sclL-2) therapy in an HIV-infected Thai population. Design: Seventy-two patients with baseline CD4 cell count of ≥ 350 x 106/l and no history of opportunistic infection were randomized to receive antiretroviral therapy plus scIL-2 (scIL-2 group) or antiretroviral therapy alone (control group). scIL-2 was administered at one of three doses for at least 24 weeks. The main measure of treatment efficacy was change in CD4 cell count. Results: The time-weighted mean change in CD4 cell count from baseline to week 24 was + 252 x 106/l for the scIL-2 group compared with + 42 x 106/l for the control group (P< 0.0001). Changes in plasma HIV RNA were not significantly different between the groups over the same time period: there was a 0.83 log10 copies/ml decrease for the sclL-2 group and a 0.70 log copies/ml decrease for the control group (P = 0.362). Conclusions: This study provides the most extensive experience of sclL-2 therapy in HIV-1 infected women and Asians, and demonstrates the immunological efficacy, tolerability and feasability of sclL-2 therapy in this population. Data from this study were instrumental in guiding the selection of the sclL-2 dosing regimen for ongoing phase III trials. (C) 2000 Lippincott Williams and Wilkins.